Global prevalence of Candida species diversity in oral cavity of denture wearing patients- A systematic review and meta analysis - Das , Duttatrayee; Bhuyan, Lipsa; Panda , Abikshyeet; Raghuvanshi, Malvika; Dash , Kailash Chandra; Mishra, Pallavi (Bangladesh Journal of Medical Science, 2025)
Aim in order to give current evidence regarding the diversity of candida species in individuals who have dentures or who suffer from denture stomatitis (DS). Methods The study was registered in PROSPERO and followed the PRISMA guidelines for systematic reviews and metaanalyses. Patients with dentures or denture stomatitis were the subjects of a comprehensive literature search that spanned the years 2000–2023. The goal was to find studies that measured the prevalence of multiple species of candida that colonise denture patients. In order to determine the studies’ quality, the Newcastle Ottawa scale (NOS) was used. Employing a random-effect model with a significance level set at p<0.05, the summary statistic measure was the odds ratio (OR) and the risk ratio (RR). Results The criteria were met by fifteen papers, twelve of which were included in the meta-analysis, and all of them underwent qualitative synthesis. All studies were thoroughly evaluated because their quality assessments showed a moderate to low risk of bias. Among 15 studies, seven studies were from American continent, five studies from Asian continent and three studies from European continent showing a wide range of candida diversity in these population. Meta-analysis revealed that American, Asian and European population with denture stomatitis (DS) had a strong association and risk of acquiring candida colonisation and infection (p<0.05). Funnel plot did not reveal presence of any publication bias in meta-analysis. Conclusion there is a need for comprehensive oral health care for denture wearing patients or denture stomatitis (DS) to monitor the candida colonization and by targeting proper preventive measures so as to improve and maintain the oral hygiene of patient. BJMS, Volume: 24. Supplementary Issue 2025, Page : 24-33